2019
DOI: 10.1101/538496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alzheimer’s disease clinical variants show distinct regional patterns of neurofibrillary tangle accumulation

Abstract: Background: Neurofibrillary tangle (NFT) pathology in Alzheimer's disease (AD) follows a stereotypic progression well-characterized by Braak staging. However, some AD cases show deviations from the Braak staging scheme. In this study, we tested the hypothesis that these variations in the regional distribution of tau pathology are linked to heterogeneity in the clinical phenotypes of AD. Methods:We included a clinicopathological cohort of ninety-four AD cases enriched for atypical clinical presentations. Subjec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 46 publications
5
33
1
1
Order By: Relevance
“…This confirms our previous findings within atypical AD, 38 and another study that found greater neocortical flortaucipir uptake in younger age participants 39 . It also explains why in one recent pathological study, higher neurofibrillary tangle burden was found in the Aty‐AD cases compared with Ty‐AD cases where the latter group was older 40 . This mismatch between flortaucipir uptake and volume in the relationship with age could be due to a number of different factors.…”
Section: Discussionsupporting
confidence: 89%
“…This confirms our previous findings within atypical AD, 38 and another study that found greater neocortical flortaucipir uptake in younger age participants 39 . It also explains why in one recent pathological study, higher neurofibrillary tangle burden was found in the Aty‐AD cases compared with Ty‐AD cases where the latter group was older 40 . This mismatch between flortaucipir uptake and volume in the relationship with age could be due to a number of different factors.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals presenting with PPA caused by AD pathology, for instance, tend to have a younger age at onset and to show an asymmetric distribution of NFT, 36 a higher ratio of neocortical to entorhinal tangles, 37 and a smaller influence of the APOE e4 allele as a risk factor. 38 Regarding anatomic distribution of pathology, recent clinicopathologic studies found that a higher semiquantitative burden of neuronal tau pathology in the superior and middle temporal gyrus and middle frontal gyrus in AD manifesting as a PPA syndrome, 39,40 suggesting a distinct pattern of NFT distribution in atypical AD manifestation, may reflect a cortical proposed subtype of NFT deposition. 41 Other autopsies studies unveiled comorbid conditions in cases of lvPPA with Lewy body pathology or FTLD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Murray et al have reported that, when AD autopsy cases were divided into three distinct groups based on the regional pattern of the NFT pathology observed ("hippocampal-sparing," "typical," and "limbic predominant"), there was a trend towards fewer APOE4 carriers in the "hippocampal-sparing" AD group, and there were significantly more late-onset (greater than 65 years old at diagnosis) APOE4 carriers vs. non-carriers in the "limbic predominant" AD group [61]. Although a more recent study failed to replicate this finding in a set of AD autopsy cases enriched for atypical presentation (in which APOE4 carriers were underrepresented), there did appear to be a trend (p = 0.0992) towards more APOE4 carriers among "limbic predominant" AD cases and fewer APOE4 carriers among "hippocampal-sparing" AD cases [107]. Interestingly, a recent follow-up paper by Murray and colleagues also reported that APOE4+ "typical" AD patients, as compared to APOE4− "typical" AD patients, possess more NFT pathology in their nucleus basalis of Meynert (nbM), the major source of cholinergic innervation in the brain [110].…”
Section: Apoe4 Associated With Increased Nft Deposition In Other Braimentioning
confidence: 97%